Early Impact of COVID-19 Outbreak on the Availability of Cornea Donors: Warnings and Recommendations - Toro M (Dove Medical Press, 2020)
Mario Toro,1,2 Tomasz Choragiewicz,1 Chiara Posarelli,3 Michele Figus,3 Robert Rejdak1 On Behalf of European COVID-19 Cataract Group (#EUROCOVCAT)1Department of General Ophthalmology, Medical University of Lublin, Lublin, Poland; 2Faculty of Medical Sciences, Collegium Medicum Cardinal Stefan Wyszyński University, Warsaw, Poland; 3Department of Surgical, Medical, and Molecular Pathology, and of the Critical Area, University of Pisa, Pisa, ItalyCorrespondence: Mario ToroDepartment of General Ophthalmology, Medical University of Lublin, Lublin, PolandTel +48 608047052Fax +48 815326149Email toro.mario@email.itAbstract: Keratoplasty is one of the irreplaceable treatment options for corneal diseases. Currently, there is no evidence to substantiate that harvested corneal grafts from COVID-19 patients can contain SARS-CoV-2 virus and lead to a systemic infection. Although the risk of transmission through corneal stromal tissue is low, it potentially exists. Lack of clinical data, unclear potential of donor-derived infection and non-established recommendations for transplantation during the COVID-19 pandemic have resulted in a dramatic reduction in the number of keratoplasty and cornea donors at ophthalmology departments and eye banks. To eliminate the risk of infection of recipients and medical personnel, we suggest that the blood samples of all donors should be screened with RT-PCR tests and nasopharyngeal swabs should be taken. In addition, a chest CT scan should be performed if the circulation is maintained. Moreover, the donors’ clinical and epidemiological medical history must be screened for typical symptoms and potential contact with SARS-CoV-2 carriers to reduce the risk of transmission. The Guidelines of the Eye Bank Association of America (EBAA), Global Alliance of Eye Bank Associations (GAEBA) and European Association of Tissue Banks provide useful recommendations to eliminate the risk of transmission according to previous experiences based on similar viruses.Keywords: COVID-19 pandemic, keratoplasty, transplant, ophthalmology, RT-PCR blood test, chest CT scan